Tumor immune escape mechanisms that operate during metastasis - Croci Russo, Diego Omar (2011)
Immune cells actively influence, among other factors, each step of tumor development determining the chance of a cancer cell to survive in a threaten microenvironment. Antitumor immune-mediated mechanisms are activated as soon as the first cancer cell is detected and operate both during primary tumor formation and during metastasis. However, when both innate and adaptive immunity becomes impaired, tumor development occurs. In this sense, compelling evidences indicate that tumor cells employ mechanisms that circumvent or thwart the immune response to enhance their own growth. These mechanisms include the secretion of immunosuppressive factors and the induction of distinct regulatory lymphoid or myeloid cells and, as occur with the immune response, they operate both during primary tumor formation and metastasis. Interestingly, cellular and molecular mechanisms of the immune response are important components of the tumor microenvironment and have the ability to promote or suppress tumor progression depending of the context of each cell interaction. In that sense, researchers are focusing their attention in the study of the influence of the tumor microenvironment in tumor growth and metastasis to better understand cancer biology and to formulate novel therapeutic approach. This review will focus on the present knowledge about interaction between immune cells and tumors in the context of metastasis, discussing the participation of different components of innate and adaptive immune response in the process of metastasis formation and dissemination.